2020
DOI: 10.1109/access.2020.2985261
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Authentication in Body Area Networks Using Signal Propagation Characteristics

Abstract: Developments in wireless communications and wearable devices have facilitated the emergence of a network of tiny sensors embedded in, on or around human body called Wireless Body Area Network (WBAN). Over the last decade, WBAN has increasingly been playing a vital role in modern medical systems because of its potential to revolutionize healthcare delivery. The data collected by the sensors contain sensitive information and are transmitted via wireless channels. However, the openness of these channels makes WBA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…The following cryptographic techniques concentrate on the security and privacy issues and obtained efficient results such as high reliability and accuracy. Biometrics techniques [ 19 ] Key management scheme [ 41 ] Mutual authentication scheme [ 25 ] Session key arrangement scheme [ 39 ] Elliptical Curve cryptography [ 11 ] Lightweight Scheme [ 31 ] Trust management scheme [ 29 ] …”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The following cryptographic techniques concentrate on the security and privacy issues and obtained efficient results such as high reliability and accuracy. Biometrics techniques [ 19 ] Key management scheme [ 41 ] Mutual authentication scheme [ 25 ] Session key arrangement scheme [ 39 ] Elliptical Curve cryptography [ 11 ] Lightweight Scheme [ 31 ] Trust management scheme [ 29 ] …”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…The techniques involved in machine learning and regression algorithms to obtain accurate results and lesser resource overhead. Umar et al [ 25 ] suggested the signal propagation-based mutual authentication scheme to detect active and passive network attacks. Active attacks manipulate the entire content of the data transmission, such as adding extra characters and spacing between them.…”
Section: Research Issues In Secure Wbanmentioning
confidence: 99%
“…However, due to the openness of the wireless channel, the data transmitted in WBAN can easily be eavesdropped or tampered with by unauthorized users. Since these sensitive patient data are the basis of clinical diagnosis, any data leakage or modification may put the patient's life at risk [3][4][5]. Consequently, it is necessary and important to provide a safe and reliable authentication protocol in the WBAN to ensure that only legitimate users can obtain the patient's sensitive information.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of papers [17], [30] presented the authentication schemes based on channel characteristics. Such schemes are good for providing key entropy based on channel variation which results in robust authentication.…”
Section: Introductionmentioning
confidence: 99%